How to build your own - Marshall, Noel. (Ireland : Marshall Tools Ltd., 2007)
Who pioneered the bricky & mason's mate range of building tools brings you this two hour comprehensive production. With absolute clarity it takes you through all stages of constructing and independent building, built to the same standard as your own home, in line with current building regulations.
Naratted by Noel Marshall.
Keywords: Building -- Amateurs' manuals; House construction -- Amateurs' manuals